2018
DOI: 10.3892/mmr.2018.8442
|View full text |Cite
|
Sign up to set email alerts
|

Let-7b regulates alpaca hair growth by downregulating ectodysplasin A

Abstract: Hypohidrotic ectodermal dysplasia (HED), also known as anhidrotic ectodermal dysplasia, is characterized by the clinical manifestations of less sweat or no sweat, sparse or no hair, tooth agenesis and/or abnormal tooth morphology. The characteristics of alpaca ear hair differ from the back hair. The ectodysplasin A (EDA) signaling pathway has a regulatory effect on skin development and hair growth. The aim of the present study was to study the effects of EDA on alpaca hair growth by examining the mRNA and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, HFD can accelerate both the anagen and telogen phases, shorten the hair growth cycle, and induce lipid droplet accumulation, ROS generation, and NF-κB signaling pathway activation in hair follicle stem cells (Morinaga et al, 2021). Liu et al (2018) revealed that EDA mRNA and protein expression was higher in ear skin than in back skin. Moreover, alpaca ear hair is thick and straight with a long growth cycle, but its back hair is long, curved, and has a short growth cycle (Liu et al, 2011); these differences in growth cycle duration between the alpaca ear and back hair may be related to differential EDA expression.…”
Section: The Role Of Ectodysplasin a In Hair Developmentmentioning
confidence: 99%
“…Furthermore, HFD can accelerate both the anagen and telogen phases, shorten the hair growth cycle, and induce lipid droplet accumulation, ROS generation, and NF-κB signaling pathway activation in hair follicle stem cells (Morinaga et al, 2021). Liu et al (2018) revealed that EDA mRNA and protein expression was higher in ear skin than in back skin. Moreover, alpaca ear hair is thick and straight with a long growth cycle, but its back hair is long, curved, and has a short growth cycle (Liu et al, 2011); these differences in growth cycle duration between the alpaca ear and back hair may be related to differential EDA expression.…”
Section: The Role Of Ectodysplasin a In Hair Developmentmentioning
confidence: 99%
“…Recent study demonstrated that let-7b stimulates differentiation and prevents metaplasia by regulating HNF6 expression in pancreatic acinar cells [ 14 ]. It is also becoming increasingly recognized that let-7b plays an important role in hair growth [ 15 , 16 ], cutaneous wound healing [ 17 ] and skin disease [ 18 ]. Recently, it was found that let-7b inhibits keratinocyte migration through targeting IGF2BP2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an alpaca model, the expression level of the miRNA let-7b was shown to be negatively correlated with EDA expression levels in ear and back hair. Overexpression of let-7b causes reductions in EDA mRNA and protein levels, indicating that let-7b regulates HF development in alpaca cells by targeting the EDA gene, which is also associated with hypohidrotic ectodermal dysplasia ( Liu et al, 2018 ). Let-7b also modulates EDA expression by post-transcriptionally regulating TGF-β receptor I via a different mechanism ( Yan et al, 2016 ).…”
Section: Characteristics Of Non-coding Rnamentioning
confidence: 99%